2016
DOI: 10.1007/s00170-016-9007-4
|View full text |Cite
|
Sign up to set email alerts
|

Temperature measurements during friction stir welding

Abstract: The increasing industrial demand for lighter, more complex and multi-material components supports the development of novel joining processes with increased automation and process control. Friction stir welding (FSW) is such a process and has seen a fast development in several industries. This welding technique gives the opportunity of automation and online feedback control, allowing automatic adaptation to environmental and geometrical variations of the component. Weld temperature is related to the weld qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Studies have indicated a direct link between weld temperature and mechanical behaviour of a friction stir weld joint. Microstructural evolution, defects, corrosion, wear and mechanical properties are all direct consequences of temperature distributions during welding and are often determined by processing parameters employed during the welding [5][6][7][8][9][10]. Microstructural changes during FSW has been reported by various researchers [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated a direct link between weld temperature and mechanical behaviour of a friction stir weld joint. Microstructural evolution, defects, corrosion, wear and mechanical properties are all direct consequences of temperature distributions during welding and are often determined by processing parameters employed during the welding [5][6][7][8][9][10]. Microstructural changes during FSW has been reported by various researchers [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, high demands on the design of the measuring device and the permanent transmission of the electrical voltage are necessary [2]. The measurement of the joining zone temperature during the process is an increasingly quantifiable indicator, as it allows conclusions to be drawn about the heat input and thus the thermomechanical stress on the microstructure [2][3][4]. Temperatures are currently measured by thermography or thermocouples, which are integrated into the welding tool [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the latter method is very costly and inaccurate, as the thermocouple does not contact the friction point between the shoulder of the tool and the workpiece. In addition, various publications have described that the thermocouples were either destroyed or changed in their position during the welding process so that an exact temperature measurement was not possible [3]. Measurement deviations and time delays can occur due to heat conduction in the tool or the heat transfer to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Fine grains are constructed behind the tool due to dynamic recrystallization. Advancing motion of the tool generates transverse loads parallel to the direction of linear motion; in addition, normal exerted force is the force required for the shoulder of tool to remain in contact with the weld piece [6][7][8]. [9] Many researchers have investigated the FSW of AA6061-T651.…”
Section: Introductionmentioning
confidence: 99%